PENEGAKAN HUKUM PIDANA TERHADAP PENGGUNA NARKOTIKA SEBAGAI PELAKU TINDAK PIDANA NARKOTIKA DI POLRESTA MEDAN - Victor Ziliwu; Syafruddin Kalo; Mahmud Mulyadi; Madiasa Ablisar (USU LAW JOURNAL, 2016)
ABSTRACT Law on Narcotics and Psychotropic Substances Act mandates an obligation to undergo treatment and the treatment and rehabilitation of drug addicts. The provisions concerning the "obligation" to undergo rehabilitation for users who experience addiction, in the Psychotropic Law stipulated in Article 36 s / d of Article 39 and the Narcotics Act under Article 45. Users of narcotics as criminals and at the same time as the victim, based on Article 103 Narcotics Act, the Supreme Court issued a breakthrough by issuing several circulars, among others: Circular of the Supreme Court (SEMA) No. 07 Year 2009 concerning the Placing to Drug Users In Nursing and Rehabilitation Therapy contained into Letter No. 07 / BUA.6 / HS / SP / III / 2009 dated March 17, 2009 (hereinafter referred to as SEMA No. 07 of 2009); and Circular of the Supreme Court (SEMA) No. 04 Year 2010 concerning the Stipulation of abuse, and to the Narcotic Addict Rehabilitation In the Institute of Medical and Social Rehabilitation (hereinafter referred to as SEMA No. 04 of 2010). As a result of SEMA No. 07 in 2009 and continued with the SEMA No. 04 The year 2010 is associated with criminal law enforcement against drug users as criminals narcotics in Medan Police, the Investigator difficulty determining whether a person is caught red-handed with evidence under SEMA No. 07 The year 2009 belongs to the category of users or addicts. Because both are victims of crime as narcotic crime. The difficulty occurs because many actors are caught with evidence of drugs as defined in the SEMA No.